Polymer elastomer as well as preparation method and application thereof

By preparing a polymer elastomer that can use temperature difference to convert heat into electrical energy, the problem of traditional flexible strain sensors requiring external power is solved, and the self-powering function and excellent mechanical properties are achieved. It is suitable for sensor applications without power supply environments.

CN119463028APending Publication Date: 2025-02-18YUNNAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411333723.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional flexible strain sensors require external power supplies, resulting in high energy consumption and poor portability, limiting their application in wearable and micro devices.

Method used

By mixing cellulose with eutectic solvents to build a hydrogen bond network, introducing acrylic anhydride compounds for esterification, and in situ radical polymerization with acrylic monomers, a polymer that can convert heat into electrical energy using temperature difference is prepared. Elastomer.

Benefits of technology

It realizes self-powered function, no external power supply is required, suitable for environments without power supply or difficult to wiring, reduces dependence on traditional batteries, extends the service life of the sensor, and has excellent mechanical properties and adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463028A_ABST
    Figure CN119463028A_ABST
Patent Text Reader

Abstract

The invention provides a polymer elastomer and a preparation method and application thereof, and relates to the field of self-powered strain sensors. The preparation method of the polymer elastomer provided by the invention comprises the following steps: mixing cellulose and a deep eutectic solvent, and carrying out hydrogen bond bonding to obtain a hydrogen bond network system; mixing the hydrogen bond network system with an acrylic anhydride compound, and carrying out esterification reaction to obtain a modified cellulose system; and mixing the modified cellulose system, an acrylic monomer and an initiator, and carrying out in-situ free radical polymerization to obtain the polymer elastomer, the hydrogen bond donor of the deep-eutectic solvent is ethylene glycol and / or glycerol, and the hydrogen bond acceptor is choline chloride. Elastomer polymerization is carried out in an anhydrous system, the eutectic solvent is grafted to the surface of cellulose, based on the Seebeck principle, temperature difference can be generated at the two ends of the material through body temperature, potential difference is finally formed at the cold end and the hot end, and low-temperature waste heat is recycled and converted into electric energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of self-powered strain sensors, and in particular relates to a polymer elastomer and a preparation method and application thereof. Background Art

[0002] As one of the basic core devices for signal capture, strain sensors need to meet the characteristics of high sensitivity, diverse functions, self-power supply and applicability. Traditional strain sensors are limited in application in a large strain range due to their lack of flexibility, because of the unstable conductivity under large strain, the poor compatibility of conductive fillers with elastic matrix, and the low fracture strain caused by the inherent brittleness of inorganic conductive materials. At present, rigid sensors are difficult to meet the use requirements when facing complex and special signals in different environments due to their hard texture and body defects of difficult deformation. Therefore, flexible strain sensors came into being and are mostly used in smart medical care, human-computer interaction, smart agriculture, intelligent robots and other fields.

[0003] However, most of the flexible sensors currently used are hydrogel elastomers, which require an external power supply during operation. The use of external power supply will increase the energy consumption of the system, which is particularly inconvenient in application scenarios that require long-term operation or difficulty in frequent battery replacement. It also affects flexibility and portability, limiting its application in wearable devices and micro devices. Summary of the invention

[0004] The purpose of the present invention is to provide a polymer elastomer and a preparation method and application thereof. The polymer elastomer prepared by the present invention can utilize temperature difference to convert heat into electrical energy to achieve self-power supply.

[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] A method for preparing a polymer elastomer comprises the following steps:

[0007] The cellulose and the low eutectic solvent are mixed to form hydrogen bonds to obtain a hydrogen bond network system;

[0008] The hydrogen bond network system and acrylic anhydride compounds are mixed to carry out esterification reaction to obtain a modified cellulose system;

[0009] The modified cellulose system, acrylic monomer and initiator are mixed to perform in-situ free radical polymerization to obtain the polymer elastomer;

[0010] The hydrogen bond donor of the deep eutectic solvent is ethylene glycol and / or glycerol, and the hydrogen bond acceptor is choline chloride.

[0011] Preferably, the molar ratio of hydrogen bond donor to hydrogen bond acceptor in the deep eutectic solvent is 1 to 3:1;

[0012] The mass ratio of the cellulose to the low eutectic solvent is 0.01-0.04:1.

[0013] Preferably, the hydrogen bonding temperature is 100-110° C. and the time is 2-3 h.

[0014] Preferably, the acrylic anhydride compound is methacrylic anhydride;

[0015] The temperature of the esterification reaction is 90-120° C. and the time is 10-40 minutes.

[0016] Preferably, the acrylic monomer includes one or more of acrylic acid, methacrylic acid and hydroxymethylacrylic acid;

[0017] The molar ratio of the acrylic monomer to the hydrogen bond acceptor in the deep eutectic solvent is 0.5 to 2:1;

[0018] The mass ratio of the initiator to the acrylic monomer is 0.05 to 0.1:1.

[0019] Preferably, the temperature of the in-situ free radical polymerization is 90-100° C., and the time is 65-110 min.

[0020] Preferably, the cellulose is polyphenol-modified cellulose.

[0021] Preferably, the method for preparing the polyphenol-modified cellulose comprises: mixing cellulose and polyphenol and performing hydrogen bonding.

[0022] The present invention also provides a polymer elastomer prepared by the preparation method described in the above technical solution.

[0023] The present invention also provides the use of the polymer elastomer described in the above technical solution or the polymer elastomer prepared by the preparation method described in the above technical solution in self-powered materials, waste heat recovery materials or antibacterial materials.

[0024] The present invention provides a method for preparing a polymer elastomer, comprising the following steps: mixing cellulose and a low eutectic solvent, performing hydrogen bonding, and obtaining a hydrogen bond network system; mixing the hydrogen bond network system and an acrylic anhydride compound, performing an esterification reaction, and obtaining a modified cellulose system; mixing the modified cellulose system, an acrylic monomer, and an initiator, and performing in-situ free radical polymerization to obtain the polymer elastomer; the hydrogen bond donor of the low eutectic solvent is ethylene glycol and / or glycerol, and the hydrogen bond acceptor is choline chloride. The present invention mixes cellulose and a low eutectic solvent to construct a dense hydrogen bond supramolecular physical network; introduces acrylic ester bonds on the surface of cellulose to construct a chemical cross-linking network; and then uses a "one-pot method" to perform in-situ free radical polymerization with acrylic monomers. Among them, the low eutectic solvent is a mixture of choline chloride and hydrogen bond receptors. The low eutectic solvent is grafted on the surface of cellulose. The choline chloride in the introduced low eutectic solvent can dissociate into choline cations and chloride ions. Based on the Seebeck principle, the resulting polymer elastomer is used as a wearable device, which can use the body temperature of the human body to form a temperature difference at both ends of the material, resulting in a difference in the movement rate of anions and cations, and eventually the anions will be enriched at the hot end, and the cations will be enriched at the cold end, forming a potential difference, realizing the recovery of low-temperature waste heat and converting it into electrical energy to power the sensor. The resulting polymer elastomer does not require an external power supply in the design, and can complete sensing and signal output only through temperature difference. It is suitable for environments without power or difficult wiring, making it suitable for remote and extreme environments, reducing dependence on traditional batteries and extending the service life of the sensor. In addition, the low eutectic solvent has similar physical and chemical properties to ionic liquids, has low cost and excellent biocompatibility, and is in line with the principles of green chemistry.

[0025] In addition, low eutectic solvents can significantly reduce the crystallinity of nanocellulose, which is beneficial to improving the flexibility of conductive polymers. Acrylate bonds are introduced on the cellulose surface to provide active sites for subsequent reactions, and then in situ free radical polymerization is carried out with acrylic monomers, which is beneficial to enhance the tensile strength of the polymer elastomer and increase the elasticity and adhesion of the material. The resulting polymer elastomer can be prepared as a flexible strain sensor due to its excellent mechanical properties and adhesion, and human body movement monitoring can be achieved based on resistance changes.

[0026] At the same time, the present invention utilizes the polyphenol hydroxyl structure of the polyphenol itself, which is easy to combine with the hydroxyl groups on the surface of cellulose, and can construct a hydrogen bond network, significantly reduce the eutectic point of the polymer elastomer, and give the polymer elastomer antifreeze properties, so that it can be used under extreme conditions of -24°C; and the constructed hydrogen bond network can also effectively improve the flexibility of the polymer elastomer; at the same time, polyphenol has excellent antibacterial properties, which can effectively reduce the enrichment of microorganisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0028] Figure 1 It is a comparison chart of the Seebeck coefficients of the polymer elastomers prepared in Example 4 and Comparative Example 1;

[0029] Figure 2 This is a comparison chart of the antibacterial effects of the polymer elastomers prepared in Example 4 and Example 5 on Escherichia coli and Staphylococcus aureus;

[0030] Figure 3 A comparison diagram of stress / strain curves of polymer elastomers prepared in Example 4 and Example 5;

[0031] Figure 4 is a stress-strain cyclic compression curve diagram of the polymer elastomer prepared in Example 4;

[0032] Figure 5 A digital photograph of the adhesion test of the polymer elastomer prepared in Example 4;

[0033] Figure 6 This is a resistance signal diagram of the polymer elastomer prepared in Example 4 used for human heart sensing;

[0034] Figure 7 This is a diagram of the resistance signal of the polymer elastomer prepared in Example 4 sensed at different temperatures. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a polymer elastomer, comprising the following steps:

[0036] The cellulose and the low eutectic solvent are mixed to form hydrogen bonds to obtain a hydrogen bond network system;

[0037] The hydrogen bond network system and acrylic anhydride compounds are mixed to carry out esterification reaction to obtain a modified cellulose system;

[0038] The modified cellulose system, acrylic monomer and initiator are mixed to perform in-situ free radical polymerization to obtain the polymer elastomer;

[0039] The hydrogen bond donor of the deep eutectic solvent is ethylene glycol and / or glycerol, and the hydrogen bond acceptor is choline chloride.

[0040] In the present invention, unless otherwise specified, all preparation raw materials are preferably commercially available products well known to those skilled in the art.

[0041] The present invention mixes cellulose and a low eutectic solvent to perform hydrogen bonding to obtain a hydrogen bond network system.

[0042] In the present invention, the cellulose is preferably microcrystalline cellulose, nanocellulose or polyphenol-modified cellulose; the nanocellulose is preferably TEMPO-oxidized nanocellulose; and the polyphenol-modified cellulose is preferably polyphenol-modified microcrystalline cellulose or polyphenol-modified nanocellulose.

[0043] In the present invention, the hydrogen bond donor of the deep eutectic solvent is ethylene glycol and / or glycerol. In a specific embodiment, the hydrogen bond donor of the deep eutectic solvent can be ethylene glycol and glycerol, ethylene glycol or glycerol; the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor in the deep eutectic solvent is preferably 1 to 3:1, and in a specific embodiment, it can be 1:1, 1.5:1, 2:1 or 3:1. The present invention uses ethylene glycol and / or glycerol as hydrogen bond donors with excellent self-powering performance.

[0044] In the present invention, the low eutectic solvent is preferably prepared by mixing a hydrogen bond donor and a hydrogen bond acceptor; the mixing temperature is preferably 60 to 100°C, and in a specific embodiment, it can be 60°C, 80°C or 100°C; the time is preferably 10 to 60 min, and in a specific embodiment, it can be 10 min, 30 min or 60 min; the mixing is preferably carried out under stirring conditions, and the present invention has no special limitation on the stirring rate.

[0045] In the present invention, the mass ratio of cellulose to the low eutectic solvent is 0.01 to 0.04:1. In a specific embodiment, the mass ratio can be 0.01:1, 0.02:1 or 0.04:1.

[0046] In the present invention, the temperature of the hydrogen bonding is preferably 100-110°C, and in a specific embodiment, it can be 100°C, 105°C or 110°C; the time of the hydrogen bonding is preferably 1-3h, and in a specific embodiment, it can be 1h, 2h or 3h; the hydrogen bonding is preferably carried out under stirring conditions.

[0047] In the present invention, the cellulose is preferably polyphenol-modified cellulose; the preparation method of the polyphenol-modified cellulose preferably comprises: mixing cellulose and polyphenol and performing hydrogen bonding.

[0048] In the present invention, the polyphenols preferably include one or more of tannic acid, ellagic acid and gallic acid; the cellulose is preferably used in the form of a cellulose aqueous dispersion; the solid-to-liquid ratio of cellulose to water in the cellulose aqueous dispersion is preferably 0.01-0.2 g / mL, and in a specific embodiment, it can be 0.03 g / mL, 0.1 g / mL or 0.2 g / mL; the pH value of the cellulose aqueous dispersion is preferably 7.4-8.5, and in a specific embodiment, it can be 7.4, 7.6, 8, 8.3 or 8.5. In the present invention, if the pH of the cellulose aqueous dispersion is not within the above range, the cellulose aqueous dispersion is preferably pH-adjusted; the pH-adjusting agent is preferably sodium hydroxide; and the concentration of the sodium hydroxide is preferably 0.1-1M.

[0049] In the present invention, the mass ratio of the polyphenol to the cellulose is preferably 0 to 0.2:1, and the polyphenol is not 0. In specific embodiments, it can be 0.05:1, 0.1:1 or 0.2:1.

[0050] In the present invention, the temperature of the hydrogen bonding is preferably room temperature; the time is preferably 12 to 96 hours, and in a specific embodiment, it can be 12 hours, 20 hours, 48 ​​hours, 70 hours or 96 hours; the hydrogen bonding is preferably carried out under stirring conditions; the hydrogen bonding is also preferably centrifuged and dried; the centrifugal speed is preferably 5000 to 8000 rpm, and in a specific embodiment, it can be 5000 rpm, 6000 rpm or 8000 rpm; the centrifugation time is preferably 15 to 30 minutes, and in a specific embodiment, it can be 15 minutes, 20 minutes or 30 minutes; the drying includes discarding the supernatant after the product after centrifugation and drying to constant weight; the drying is preferably vacuum drying, the temperature is preferably 60 to 80°C, and in a specific embodiment, it can be 60°C, 70°C or 80°C; the time is preferably 48 to 60 hours, and in a specific embodiment, it can be 48 hours, 55 hours or 60 hours. The elastomer polymerization system in the present invention is anhydrous. Water will destroy the supramolecular hydrogen bond network of the polymer, thereby affecting the antifreeze property of the material. Therefore, the above conditions are used to fully dry the system.

[0051] After obtaining the hydrogen bond network system, the present invention mixes the hydrogen bond network system with an acrylic anhydride compound to carry out an esterification reaction to obtain a modified cellulose system.

[0052] In the present invention, the acrylic anhydride compound is preferably methacrylic anhydride; the mass ratio of the cellulose to the acrylic anhydride compound is preferably 1:2-5; in a specific embodiment, it can be 1:2, 1:3 or 1:4.5.

[0053] In the present invention, the temperature of the esterification reaction is preferably 90-120°C, and in a specific embodiment, it can be 100°C, 110 or 120°C; the time of the esterification reaction is preferably 10-40 min, and in a specific embodiment, it can be 10 min, 20 min, 30 min or 40 min.

[0054] After obtaining the modified cellulose system, the present invention mixes the modified cellulose system, acrylic monomers and an initiator to perform in-situ free radical polymerization to obtain the polymer elastomer;

[0055] In the present invention, the acrylic monomer preferably includes one or more of acrylic acid, methacrylic acid and hydroxymethyl acrylic acid, and in a specific embodiment, it can be acrylic acid, methacrylic acid or hydroxymethyl acrylic acid; the initiator is preferably a photoinitiator I2959; the molar ratio of the acrylic monomer to the hydrogen bond acceptor in the low eutectic solvent is 0.5 to 2:1, and in a specific embodiment, it can be 0.5:1, 1:1 or 2:1; the mass ratio of the initiator to the acrylic monomer is preferably 0.05 to 0.1:1, and in a specific embodiment, it can be 0.05:1, 0.08:1 or 0.1:1.

[0056] In the present invention, the temperature of the in-situ free radical polymerization is preferably 90-100°C, and the time is preferably 65-110 min; the in-situ free radical polymerization is preferably carried out in a first stage reaction after adding an acrylic monomer, and in a second stage reaction after adding an initiator; the time of the first stage reaction is preferably 60-90 min, and in a specific embodiment, it can be 60 min, 70 min, 80 min or 90 min; the time of the second stage reaction is preferably 5-20 min, and in a specific embodiment, it can be 5 min, 10 min or 20 min; the in-situ free radical polymerization is preferably carried out under stirring conditions.

[0057] In the present invention, after the in-situ free radical polymerization, the obtained product is preferably cured; the curing is preferably UV curing; the wavelength of the UV curing light is preferably 280 to 365 nm, and in a specific embodiment, it can be 280 nm, 300 nm, 330 nm or 365 nm; the light power of the UV curing light is preferably 160 to 1000 mW / cm 2 In a specific embodiment, it can be 160W / cm 2 、300W / cm 2 , 500W / cm 2 , 800W / cm 2 or 1000W / cm 2The UV curing time is preferably 10 to 30 seconds, and in a specific embodiment, it can be 10 seconds, 20 seconds or 30 seconds; the UV curing is preferably carried out in a silicone mold.

[0058] The present invention mixes cellulose and a low eutectic solvent to construct a dense hydrogen-bonded supramolecular physical network; introduces an acrylate bond on the surface of cellulose to construct a chemical cross-linked network; and then uses a "one-pot method" to perform in-situ free radical polymerization with acrylic monomers. Among them, the low eutectic solvent is a mixture of choline chloride and a hydrogen bond receptor, and the low eutectic solvent is grafted on the surface of cellulose. The choline chloride in the introduced low eutectic solvent can be dissociated into choline cations and chloride ions. Based on the Seebeck principle, the obtained polymer elastomer is used as a wearable device, which can use the body temperature of the human body to form a temperature difference at both ends of the material, generate a difference in the movement rate of anions and cations, and finally the anions will be enriched at the hot end, and the cations will be enriched at the cold end, forming a potential difference, realizing the recovery of low-temperature waste heat and converting it into electrical energy to power the sensor. The obtained polymer elastomer does not require an external power supply in the design, and can complete sensing and signal output only through temperature difference. It is suitable for environments without power or difficult wiring, making it suitable for remote and extreme environments, reducing dependence on traditional batteries, and extending the service life of the sensor. Moreover, deep eutectic solvents have similar physical and chemical properties to ionic liquids, are low-cost and have excellent biocompatibility, and are in line with the principles of green chemistry.

[0059] In addition, low eutectic solvents can significantly reduce the crystallinity of nanocellulose, which is beneficial to improving the flexibility of conductive polymers. Acrylate bonds are introduced on the cellulose surface to provide active sites for subsequent reactions, and then in situ free radical polymerization is carried out with acrylic monomers, which is beneficial to enhance the tensile strength of the polymer elastomer and increase the elasticity and adhesion of the material. The resulting polymer elastomer can be prepared as a flexible strain sensor due to its excellent mechanical properties and adhesion, and human body movement monitoring can be achieved based on resistance changes.

[0060] The present invention utilizes the polyphenol hydroxyl structure of the polyphenol itself, which is easy to combine with the hydroxyl groups on the surface of cellulose, and can construct a hydrogen bond network, significantly reduce the eutectic point of the polymer elastomer, and give the polymer elastomer antifreeze properties, so that it can be used under extreme conditions of -24°C; and the constructed hydrogen bond network can also effectively improve the flexibility of the polymer elastomer; at the same time, the polyphenol has excellent antibacterial properties and can effectively reduce the enrichment of microorganisms.

[0061] The preparation method of the polymer elastomer of the present invention constructs a flexible conductive network in a three-dimensional cross-linked framework, synthesizes a poly-low eutectic solvent conductive elastomer through a simple polymerization method, designs and constructs an anhydrous polymer network with both dynamic and reversible properties, and prepares a series of multifunctional, recyclable anhydrous poly-low eutectic solvent elastic conductive materials based on biomass, which can be used to develop flexible electronic devices that can collect human body low-temperature waste heat and self-power. The steps are simple, in line with the principles of green chemistry, do not require large-scale equipment, are conducive to later industrial preparation, and can be further promoted and used.

[0062] The present invention also provides a polymer elastomer prepared by the preparation method described in the above technical solution.

[0063] In the present invention, the electrical conductivity of the polymer elastomer is preferably 3.76-4.82 mS / cm, and in a specific embodiment, it can be 3.76 mS / cm, 4 mS / cm, 4.4 mS / cm or 4.82 mS / cm; the Seebeck coefficient is preferably 16-25.68 mV / K, and in a specific embodiment, it can be 16 mV / K, 19 mV / K, 22 mV / K or 25.68 mV / K; the elongation at break is preferably 1363-2670%, and in a specific embodiment, it can be 1363%, 1800%, 2200% or 2670%.

[0064] The polymer elastomer provided by the present invention has excellent hot spot performance, good mechanical properties, certain adhesion, high strain sensing sensitivity, and still has excellent sensing performance under extreme conditions.

[0065] The present invention also provides the use of the polymer elastomer described in the above technical solution or the polymer elastomer prepared by the preparation method described in the above technical solution in self-powered materials, waste heat recovery materials or antibacterial materials.

[0066] In the present invention, the polymer elastomer is preferably used in a self-powered strain sensor; the present invention does not have any special limitation on the application process of the polymer elastomer in the self-powered strain sensor, and a process familiar to those skilled in the art may be used.

[0067] In order to further illustrate the present invention, the polymer elastomer provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0068] Example 1

[0069] 1.0027 of nanocellulose was dispersed in 30 mL of deionized water to obtain a nanocellulose dispersion; the pH value of the nanocellulose dispersion was adjusted to 8.5 using a 0.1 M sodium hydroxide solution, 0.0501 g of tannic acid was added, the mixture was mixed evenly, and the mixture was reacted at room temperature and stirred for 48 h. The obtained product was centrifuged at 5000 rpm for 15 min, the supernatant was discarded, and the mixture was vacuum dried to a constant weight to obtain polyphenol-modified cellulose;

[0070] Mix 6.9817 g of choline chloride and 5.6 mL of ethylene glycol, and stir in a 60°C constant temperature oil bath for 30 min until a uniform and transparent choline chloride-based deep eutectic solvent is obtained;

[0071] The above 7.44 g of choline chloride-based deep eutectic solvent and 0.0744 g of polyphenol-modified cellulose were uniformly mixed, reacted at 110° C. with stirring for 2 h, then the resulting reaction solution was cooled to 100° C., 0.334 g of methacrylic anhydride was added, mixed uniformly, and stirred for 20 min to obtain modified nanocellulose;

[0072] The obtained reaction solution was cooled to 90°C, 4 mL of acrylic acid was added, and the reaction was stirred at 90°C for 1 h. 0.2136 g of photoinitiator I2959 was added, mixed evenly, and stirred for 10 min. The obtained reaction solution was transferred to a silicone mold, and the wavelength of the UV lamp in the UV curing box was set to 365 nm and the power to 800 mW / cm 2 The concentration was set to 20% and UV-cured for 10 seconds to obtain a polymer elastomer, which was designated as PDES-TMCC1.

[0073] Example 2

[0074] A polymer elastomer was prepared by referring to the preparation method of Example 1, except that the mass of tannic acid was 0.1003 g. The obtained polymer elastomer was recorded as PDES-TMCC2.

[0075] Example 3

[0076] A polymer elastomer was prepared by referring to the preparation method of Example 1, except that the mass of tannic acid was 0.1504 g. The obtained polymer elastomer was recorded as PDES-TMCC3.

[0077] Example 4

[0078] A polymer elastomer was prepared by referring to the preparation method of Example 1, except that the mass of tannic acid was 0.2005 g. The obtained polymer elastomer was recorded as PDES-TMCC4.

[0079] Example 5

[0080] A polymer elastomer was prepared by referring to the preparation method of Example 1, except that no tannic acid modification was performed. The obtained polymer elastomer was recorded as PDES-MCC.

[0081] Example 6

[0082] The polymer elastomer was prepared by referring to the preparation method of Example 1, except that tannic acid was replaced by ellagic acid, the mass of ellagic acid was 0.2005 g, and the obtained polymer elastomer was recorded as PDES-EMCC4.

[0083] Example 7

[0084] The polymer elastomer was prepared by referring to the preparation method of Example 1, except that gallic acid was used instead of tannic acid, the mass of gallic acid was 0.2005 g, and the obtained polymer elastomer was recorded as PDES-GMCC4.

[0085] Example 8

[0086] The polymer elastomer was prepared by referring to the preparation method of Example 1, except that 6.9817 g of choline chloride and 7 mL of glycerol were mixed and stirred in a constant temperature oil bath at 60° C. until a uniform and transparent choline chloride-based low eutectic solvent was obtained. The obtained polymer elastomer was recorded as PDES-Gly.

[0087] Comparative Example 1

[0088] The polymer elastomer was prepared by referring to the preparation method of Example 1, except that 6.9817 g of choline chloride and 6.0060 g of urea were mixed and stirred in a constant temperature oil bath at 80° C. until a uniform and transparent choline chloride-based low eutectic solvent was obtained. The obtained polymer elastomer was recorded as PDES-Urea.

[0089] Test Case

[0090] A method for testing the self-powered performance of an ultra-flexible conductive polymer elastomer comprises the following steps:

[0091] The properties of the polymer elastomers prepared in Examples 1 to 5 and Comparative Example 1 were tested, and the specific testing methods are as follows:

[0092] The polymer elastomer was made into a circular conductor with a diameter of 15.8 mm and a thickness of 1 mm. The resistance of the material was tested using the AC impedance spectroscopy method to obtain the conductivity data. The thermal conductivity of the material was tested using the transient plate method.

[0093] At room temperature and relative humidity of 60%, the Seebeck coefficient of the polymer elastomer was tested by using a temperature patrol meter in conjunction with a multimeter. The temperature difference between the two ends of the polymer was established using a cold end heat sink, and the temperature difference between the two ends of the material was monitored and recorded using a temperature patrol meter. At the same time, the potential difference between the hot and cold ends of the material was measured using a multimeter, and the voltage change with temperature was observed in the range of 0 to 15K.

[0094] The antibacterial effect of polymer elastomer on Escherichia coli and Staphylococcus aureus was determined according to the standard ASTM E2180. The specific method was as follows: Escherichia coli and Staphylococcus aureus were first inoculated into LB liquid culture medium and cultured in a 37°C incubator at a constant temperature of 14 h. 6 The bacterial suspension of CFU / mL was diluted 100 times with PBS buffer and then inoculated onto the surface of the solid nutrient medium. The polymer elastomer was placed and cultured in a 28°C incubator for 24 hours. The culture dish was taken out and photographed to measure the size of the inhibition zone.

[0095] The antibacterial effect of polymer elastomer on Escherichia coli and Staphylococcus aureus was determined according to the standard ASTM E2180. The specific method is as follows: first, Escherichia coli and Staphylococcus aureus were spread on the surface of an agar plate and cultured in a 37°C incubator at a constant temperature of 6 h. Then, the polymer elastomer was added to the culture medium and incubated with the bacteria for 10 h. 6 The bacterial suspension of CFU / mL was diluted with PBS buffer to 10 6 times, then inoculate the bacterial suspension dilution onto the surface of the solid nutrient medium, incubate in a 28°C incubator for 24 hours, take out the culture dish, take pictures and count;

[0096] The elasticity of the polymer elastomer is tested by a universal mechanical testing machine. The polymer elastomer used for the test is a cylindrical sample (the sample diameter is 20 mm and the thickness is 10 mm). The strain rate is 10 mm / min, the fixed compression strain is 40%, and the cycle test is 10 cycles. When the cycle reaches the 10th cycle, the deformation recovery rate of the polymer elastomer is measured.

[0097] The stress / strain properties of the polymer elastomer were tested by a universal mechanical testing machine according to ASTM D638; the polymer elastomer used for the test was a rectangular sample (length 125 mm, width 13 mm, thickness 10 mm), the strain rate was 50 mm / min, and the load was 500 N;

[0098] The comparison of the Seebeck coefficients of the polymer elastomers prepared in Example 4 and Comparative Example 1 is shown in Figure 1 The comparison of the antibacterial effects of the polymer elastomers prepared in Example 4 and Example 5 on Escherichia coli and Staphylococcus aureus is shown in Figure 2The stress / strain curve comparison diagram of the polymer elastomer prepared in Example 4 and Example 5 is shown in Figure 3 The stress-strain cyclic compression curve of the polymer elastomer prepared in Example 4 is shown in Figure 4 , the test data is shown in Table 1:

[0099] Table 1 Performance test results of polymer elastomers prepared in Examples 1 to 5 and Comparative Example 1

[0100]

[0101]

[0102] Depend on Figures 1 to 4 As shown in the data in Table 1, the self-powered performance of the material is significantly reduced by changing the hydrogen bond receptor of PDES; when tannic acid is not added, the material basically has no antibacterial properties, and the mechanical flexibility is significantly reduced; when modified with ellagic acid and gallic acid, the material has antibacterial properties, but due to the poor solubility of gallic acid, the mechanical flexibility of the material will be reduced due to uneven dispersion; by reducing the viscosity of the low eutectic solvent, the ion migration rate will be effectively improved, so that the material can obtain higher conductivity and Seebeck coefficient, thereby obtaining higher self-powered performance. By introducing plant polyphenols such as tannic acid, ellagic acid, and gallic acid, a denser hydrogen bond network is constructed through phenolic hydroxyl groups and the surface of nanocellulose, which significantly improves the mechanical flexibility of the material. At the same time, these phenolic hydroxyl groups can interact with bacterial cell walls, membranes, and other important structures. This interaction may destroy the bacterial cell walls and cell membranes, thereby inhibiting bacterial growth.

[0103] Test Example 2

[0104] One side of the polymer elastomer prepared in Example 4 was placed in contact with a rubber glove, and the other side was used to adhere to objects of different materials (such as a rubber ear bulb, metal tweezers, a 50 mL polyethylene centrifuge tube filled with water, and a 50 mL glass beaker) to test the adhesion of the polymer elastomer. The results are as follows: Figure 5 shown.

[0105] Figure 5 This is a digital photo of the adhesion test of the polymer elastomer prepared in Example 4, by Figure 5 It can be seen that the polymer elastomer prepared in the present invention exhibits excellent adhesion to rubber, metal, polyethylene, and glass materials, which is conducive to being adhered to human skin as a flexible sensor, and at the same time has the characteristic of not being easy to fall off during large-scale activities.

[0106] The polymer elastomer prepared in Example 4 was adhered to the heart of the subject, and the two ends of the material were connected to a digital bridge, and the periodic resistance change could be detected. The results are as follows: Figure 6 shown.

[0107] Figure 6 The resistance signal diagram of the polymer elastomer prepared in Example 4 for human heart sensing is shown in FIG. Figure 6 It can be seen that the monitoring time period is 600s, and the signal sending interval is 2ms. The polymer elastomer prepared in the present invention has excellent strain sensing sensitivity, and the resistance signal has excellent stability and good cyclicity.

[0108] The polymer elastomer prepared in Example 4 was placed in -24°C for 20 days, and then adhered to the human joints. The sensor signal was tested by a digital bridge to monitor the human body movement. At the same time, the polymer elastomer was placed in a 60°C oven for 10 days, and then adhered to the human joints. The sensor signal was tested by a digital bridge to monitor the human body movement. The results are as follows: Figure 7 shown.

[0109] Figure 7 The resistance signal diagram of the polymer elastomer prepared in Example 4 at different temperatures is shown in FIG. Figure 7 It can be seen that under extreme conditions, the polymer elastomer prepared by the present invention still has excellent sensing properties. This is mainly due to the construction of a hydrogen bond supramolecular network in the polymer elastomer. Due to the weak interaction of non-covalent bonds, the supramolecular network is very sensitive to environmental changes (such as temperature, pressure, and chemical environment), showing high sensitivity, and can be used in sensors, responsive materials and other fields.

[0110] As can be seen from the above embodiments, the present invention uses plant polyphenol tannic acid to modify the surface of nanocellulose, introduces polyphenol hydroxyl structure, disperses it in a low eutectic solvent, and constructs a dense hydrogen bond supramolecular network. At the same time, the low eutectic solvent can significantly reduce the crystallinity of nanocellulose, which is beneficial to improving the flexibility of the conductive polymer; methacrylic anhydride is introduced to introduce acrylate bonds on the surface of nanocellulose to construct a chemical cross-linking network, which is beneficial to enhancing the tensile strength of the polymer. The "one-pot method" is used to mix with acrylic monomers to induce in-situ free radical polymerization, which is beneficial to increase the elasticity and adhesion of the material. Curing under ultraviolet light forms a conductive polymer with ultra-flexible elasticity. More importantly, the conductive polymer has shown practicality in wearable strain sensors and thermoelectric conversion for monitoring human body movement. Due to the excellent mechanical properties and adhesion of the conductive polymer, it can be prepared as a flexible strain sensor to realize human body movement monitoring according to resistance changes. It is worth mentioning that based on the Seebeck effect, the poly-low eutectic solvent elastomer uses temperature difference to cause anion and cation migration to realize the conversion of low-temperature waste heat into electrical energy, and can convert low-temperature waste heat into stable electrical energy output, realizing the application in the field of self-powered sensing.

[0111] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a polymer elastomer, characterized in that: The following steps are involved: The cellulose and the low eutectic solvent are mixed to form hydrogen bonds to obtain a hydrogen bond network system; The hydrogen bond network system and acrylic anhydride compounds are mixed to carry out esterification reaction to obtain a modified cellulose system; The modified cellulose system, acrylic monomer and initiator are mixed to perform in-situ free radical polymerization to obtain the polymer elastomer; The hydrogen bond donor of the deep eutectic solvent is ethylene glycol and / or glycerol, and the hydrogen bond acceptor is choline chloride.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the hydrogen bond donor to the hydrogen bond acceptor in the deep eutectic solvent is 1 to 3:1; The mass ratio of the cellulose to the low eutectic solvent is 0.01-0.04:

1.

3. The preparation method according to claim 1 or 2, characterized in that: The hydrogen bonding temperature is 100-110° C. and the time is 2-3 hours.

4. The preparation method according to claim 1, characterized in that: The acrylic anhydride compound is methacrylic anhydride; The temperature of the esterification reaction is 90-120° C. and the time is 10-40 minutes.

5. The preparation method according to claim 1, characterized in that: The acrylic monomer includes one or more of acrylic acid, methacrylic acid and hydroxymethylacrylic acid; The molar ratio of the acrylic monomer to the hydrogen bond acceptor in the deep eutectic solvent is 0.5 to 2:1; The mass ratio of the initiator to the acrylic monomer is 0.05 to 0.1:

1.

6. The preparation method according to claim 1 or 5, characterized in that: The temperature of the in-situ free radical polymerization is 90-100° C., and the time is 65-110 minutes.

7. The preparation method according to claim 1, characterized in that: The cellulose is polyphenol-modified cellulose.

8. The preparation method according to claim 7, characterized in that: The preparation method of the polyphenol-modified cellulose comprises: mixing cellulose and polyphenol and performing hydrogen bonding.

9. The polymer elastomer prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the polymer elastomer according to claim 9 or the polymer elastomer prepared by the preparation method according to any one of claims 1 to 8 in self-powered materials, waste heat recovery materials or antibacterial materials.

Citation Information

Cited By

  • Biological plastic based on cellulose ether eutectic solvent and synthetic method thereof

    CN120289712A